FRAMES OF DEMOCRACY: A SYNTAGMATIC DISSECTION OF PANCHAYAT SEASON 4 AND ITS REFLECTION ON RURAL INDIAN POLITICS AND ETHICS - Jaisal, Manish (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Set in the fictional village of Phulera, Panchayat Season 4 marks a significant shift in tone, moving from gentle humour and pastoral stillness to the noise and drama of grassroots politics. This article presents a comprehensive, narrative-driven review of the season, employing a syntagmatic analysis to examine how sequences of visual motifs and recurring campaign rituals—such as loudspeaker rallies, symbolic vegetables, and samosa-fueled gatherings—construct a cinematic grammar of rural democracy. The show captures political spectacle with charm, humour, and emotion, but in doing so, glosses over crucial socio-political realities like caste hierarchies, bureaucratic partisanship, and the gendered nature of power in Indian villages. While the characters remain lovable and their stakes relatable, the broader system they navigate appears curiously flattened and sanitised. Drawing upon critical reviews from Outlook India, The Indian Express, The Quint, and others—as well as research in rural political sociology—this article argues that Panchayat Season 4 presents democracy not as a contested process rooted in identity and struggle, but as a series of well-choreographed performances. The piece raises urgent questions: Can popular media portray the soul of rural India without muting its fractures? And can storytelling preserve its emotional warmth while offering structural insight? This review aims to explore that delicate balance.